2013
DOI: 10.1016/j.juro.2012.08.200
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Neuroprosthetic Training Improves Bladder Function After Severe Spinal Cord Injury

Abstract: BACKGROUND: Severe spinal cord injury (SCI) leads to neurogenic bladder dysfunction. We recently developeda multi-system neuroprosthetic training program (MSNT) that promotes plastic changes capable of restoring refinedlocomotion in rats with severe SCI. We investigated whether MSNTinfluences the formation of posttraumatic bladder dysfunction. MATERIALS AND METHODS: Adult rats were randomly assigned to a SCI (n=8) and to a control intact (n=4) group. SCI consisted of two opposite lateral hemisections (T7, T11)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…2), most likely reflecting the lowered activation threshold due to the chronic engagement of the neural networks in the trained rats. This result is consistent with the observation that after 8 weeks of locomotor training facilitated by epidural stimulation and pharmacological interventions the contractile responses of the bladder to filling in anesthetized spinal rats were more efficient in trained compared to untrained animals [26]. Direct acute responses to epidural stimulation, however, were not reported.…”
Section: Discussionsupporting
confidence: 91%
“…2), most likely reflecting the lowered activation threshold due to the chronic engagement of the neural networks in the trained rats. This result is consistent with the observation that after 8 weeks of locomotor training facilitated by epidural stimulation and pharmacological interventions the contractile responses of the bladder to filling in anesthetized spinal rats were more efficient in trained compared to untrained animals [26]. Direct acute responses to epidural stimulation, however, were not reported.…”
Section: Discussionsupporting
confidence: 91%
“…Locomotor training (LT) has emerged as a safe and effective therapy for post-SCI motor deficits with many benefits (cardiovascular function, strength, mobility) (9,23,43,52,84). Recent animal studies, however, have shown that LT post-SCI also improves bladder function (46,90), a finding consistent with a few reports from human SCI studies (42,48,75). For example, a recent study from our laboratory (90) has shown, using a spinal contusion model in adult male rats, functional gains of lower urinary tract function as assessed with terminal urodynamic measures after 12 wk of daily LT for a period of 60 min/day.…”
supporting
confidence: 60%
“…The overlap in the neural networks receiving these afferent projections with the networks responsible for controlling LUT function, including bladder and EUS activation, results in both acute as well as chronic changes when these perturbations are used repetitively. Results observed in both animal and human experiments demonstrate the degree to which the neural networks controlling LUT are affected when subjected to locomotor rehabilitation (Gad et al, 2014; Ward et al, 2014; Horst et al, 2013). The physiological responses generated, however, are dependent on the ‘ physiological state of all systems ’.…”
Section: Discussionmentioning
confidence: 97%
“…Animal studies have since begun to address the potential interactions between motor and autonomic functions in response to locomotor training. Interestingly, it has been shown recently that LUT function can be improved in rats undergoing locomotor training (Ward et al, 2014; Horst et al, 2013) that is enabled by the use of ES in combination with the administration of quipazine and strychnine. Specifically, enabling of locomotor-related spinal neuronal circuits by ES can influence neural networks controlling voiding with the onset of bladder emptying within seconds of the onset of the stimulation (Gad et al, 2014).…”
Section: Discussionmentioning
confidence: 99%